Millî Görüş Mefkûresinde İslâm Birliği ve D-8 -Teori ve Pratik- - Tuğrul, Talip (Muş Alparslan Üniversitesi, 2019)
Bu çalışmanın amacı, Millî Görüş mefkûresinde “İslâmbirliği” fikrinin kökenlerini, ideolojikbütünlük içerisindeki yerini ve “İslâm birliği”idealinin teorik ve D-8, MTB gibipratik taraflarını araştırmaktır. Millî Görüş Hareketi’nin “İslâm birliği” fikrini niçin kabulettiği, D-8 projesinin ne olduğu ve “Yeni Bir Dünya” hedefinin neresinde yeraldığı hususu ise araştırmanın temel problemini teşkil etmektedir.İslâm birliği ideali, Millî Görüş Hareketi’ninmedeniyet tasavvurundan kaynaklanmaktadır. İslâmî referanslara dayanan buperspektif, bütün insanlığın saadetine odaklı evrensel bir medeniyetperspektifidir. Hareketin kurucusu Prof. Dr. Necmettin Erbakan’a (1926-2011)göre günümüzde Irkçı Emperyalizm’in hâkim olduğu dünyamızın hali içler acısıdırve mevcut dünya iflas etmiştir. Bu zulüm düzeninden kurtulmanın anahtarı, hakkı üstün tutan biranlayışla “Yeni Bir Dünya”nın kurulmasıdır. Erbakan’a göre Yeni Bir Dünyaideali şu üç aşamada gerçekleşecektir: İslâm Birliği’nin çekirdeği ve ilk adımıolarak kabul edilen D-8,   bu sürecin ilkaşamasını oluşturmaktadır. İkinci aşama, bütün Müslüman ülkelerin katılımıylaoluşacak olan İslâm Birliği’dir (D-60). Üçüncü aşama ise Müslüman ülkelerle birlikte hareket edecek olan 100mazlum ülkeyle oluşturulacak birlik (D-160) olarak belirlenmiştir.  Araştırmadatarama modeli ve metin/doküman analizi yöntemi kullanılmıştır. Bu bağlamdaNecmettin Erbakan’ın eserlerinin toplandığı “Erbakan Külliyatı”, hareketindiğer yazılı kaynakları, konuyla ilgili kitaplar, makaleler ve ansiklopedi maddeleri taranmış ve elde edilen veriler analizedilmiştir. Araştırmanın sonucundaErbakan’ın “Yeni Bir Dünya” hedefi ile İslâm birliği idealinin teoridebirleştirdiği görülmüştür. Zira Millî Görüş mefkûresinin “Yeni Bir Dünya” idealinde, İslâm Birliği’ninkurucu ve belirleyici bir fonksiyonu tasavvur edilmiştir. Bu fikrin enönemli pratiği olan D-8 ile “İslâm Birliği”ideali, fikriyattan fiiliyata geçmiştir.

The aim of this study is to investigate the origins ofthe idea of “?Islamic unity”, its place in the ideological integrity and thetheoretical and practical aspects of the “Islamic unity” ideal such as D-8 andMTB within the ideal of Millî Görüş. The main problem of the research is whythe Millî Görüş Movement accepted the idea of “Islamic unity”, what the D-8project is and where it is located in the “A New World” target. The ideal of Islamic unity stems from the civilizationperspective of the Millî Görüş Movement. This perspective, based on Islamicreferences, is a universal civilization perspective focused on the bliss of allhumanity. Prof. Dr. Necmettin Erbakan (1926-2011), the founder of the movement, the state of our world, which is dominated by Racist Imperialism today, is pitiful and the currentworld is bankrupt. He thinks that the key to get rid of this order ofpersecution is the establishment of “A New World” with an understanding thatholds the right superior. According to Erbakan, the ideal of a New World willbe realized in the following three stages: D-8, which is accepted as the coreand first step of the Islamic Union, constitutes the first stage of thisprocess. The second stage is the Islamic Union (D-60), will be formed with theparticipation of all Muslim countries. The third stage is defined as the unityof the 100 oppressed countries that will act together with the Muslim countries(D-160).In the study, scanning model and text/documentanalysis method were used. In this context, “Erbakan Külliyatı”, where theworks of Necmettin Erbakan are collected, other written sources of themovement, books, articles and encyclopedia articles on the subject were scannedand the data obtained were analyzed. As a result of the research, it was seenthat Erbakan combines the ideal of “A New World” with the ideal of Islamicunity in theory. It is revealed that the Islamic Unity is a founding anddecisive stage on the way to “A New World” goal of the Millî Görüş Movement.D-8, which is the most important practice of this idea, means thetransformation of the ideal of Islamic Unity from idea to actuality.
İslamic Unity and D-8 Within the İdeal of Millî Görüş Movement -Theory and Practice-
dinbil
Keywords: İslamcılık; İslam Birliği; Milli Görüş Hareketi; Necmettin Erbakan; Çağdaş İslami Akımlar; Contemporary Islamic Movements; Islamism; Islamic Unity; Millî Görüş Movement; Necmettin Erbakan